The Effectivness of Using snake and Ladder Game to Teach Speaking Skill - Ifayatun, Zulis; Fajarina, Maskhurin (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Abstract English language has four skills: writing, listening, reading, and speaking, there are so many young people who are not confident, can not even speak English. at SMPN 1 Jombang have problems in speaking skills. The purposes of this study are to determine: the speaking skill of students before treatment. 2. the speaking skill of students after treatment. the effectiveness of the snake and ladder games media on teach speaking skills. This study used a quantitative method with a total sample was 31 students. however, children who has tooken the pre-test and post-test is 25 from the experimental class (8J). Sampling was carried out in grades 8J at SMPN 1 Jombang. The overall sampling technique used probability sampling with random sampling type, The technique of collecting data was using pre-test and post-test, in proving and analyzing the data was using validity test, descriptive statistics and paired sample test. The results experimental class before and after treatment are: 1). Pre test in the experimental class with the respondents is 25 with an average value of 43 and the lowest value of 40 and the highest score of 53. 2). The post test in experimental the average score in the experimental class was 71.72 with the lowest score of 60 and the highest score of 80. 3). Paired sample test shows that the snake and ladder game media is effective for learning English, especially for developing students' speaking skills, from the calculation of the data is 0,000 < 0,05 it means that the results of hypothesis testing, Ha is accepted, Ho is rejected. Keyword : effectiveness, speaking, snake and ladder games.